PENERAPAN MODEL PEMBELAJARAN PROBLEM BASEDINSTRUCTION (PBI) SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELASVII MTs AR-RUSYDINY TAHUNPELAJARAN 2016/2017 - Hendrawadi, Yayan; Syahrir, Syahrir; Abidin, Zainal (Media Pendidikan Matematika, 2017)
low student learning outcomes and lack of activity due to the students' learning in the learning process is more focused only on the teacher. Teachers do not fully engage students in learning. Students are more dominant as a receiver only so that students tend to passive learning. This will result in mathematics boring and unpleasant. The implication of activity and student learning was low. So that the learning process goes well it needs a setrategi active learning that engages students in the learning process that is expected to increase the activity and student learning outcomes. Therefore, this study was conducted to improve learning outcomes math class VII MTs Ar-rusydiny through the implementation of learning model of problem-basedinstruction.This type of research is a classroom action research conducted in two cycles. An instrument which is used mainly obserpasi and test sheets. From the results of research in proleh that the number of students in the activity scores 2 sisklus always increase. In the first cycle of activity percentage is 56.41% with the active category, while in the second cycle the percentage of student activity is 69, 23% to the category of active while classical completeness obtained 60% in the first cycle and 90% in the II.Hal cycle already addressed achievement research indicator that the set, so it can be concluded that through the implementation of learning model of problem-based instruction can improve students' mathematics learning outcomes kelasVII MTs Ar-rusydiny the school year 2016/2017